2022
DOI: 10.1371/journal.pone.0270245
|View full text |Cite
|
Sign up to set email alerts
|

Causes of infant deaths and patterns of associated factors in Eastern Ethiopia: Results of verbal autopsy (InterVA-4) study

Abstract: Background In a range of setting, detecting and generate empirical information on the cause of infant death and contributing risk factors at population level is basically utmost essential to take evidence-based measures in reducing infant morbidity and mortality. An electronic verbal autopsy is suitable tool and best alternative solution to determine individuals’ cause of death in a setting where the majority of deaths occur at home and civil registration systems do not exist. The present study was undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
(55 reference statements)
4
8
0
Order By: Relevance
“…Severe malnutrition and ARIP were the commonest underlying and primary causes of death respectively. This is similar to verbal autopsy studies in Ethiopia and Bangladesh where acute lower respiratory infection was the commonest cause of death [ 30 , 33 ]. In the latter study, childhood wasting was additionally identified as the leading risk factor for lower respiratory infections.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Severe malnutrition and ARIP were the commonest underlying and primary causes of death respectively. This is similar to verbal autopsy studies in Ethiopia and Bangladesh where acute lower respiratory infection was the commonest cause of death [ 30 , 33 ]. In the latter study, childhood wasting was additionally identified as the leading risk factor for lower respiratory infections.…”
Section: Discussionsupporting
confidence: 86%
“…However, in this study, only a few caretakers reported seeking care from traditional healers or pharmacies. Other studies in Ghana, Rwanda and Ethiopia found a similarly high number of home deaths [29][30][31]. With substantial proportions of deaths occurring at home, mortality data generated through the use of VA should be considered as an adjunct to data from health facilities in characterizing under-5 deaths.…”
Section: Plos Onementioning
confidence: 98%
“…The most frequently reported causes of neonatal deaths are infections, perinatal asphyxia, metabolic diseases, and congenital malformations. [9][10][11][12] In this study, natural deaths were responsible for 74.5% (n = 91) of total deaths. As a natural cause, the most common one in the group was pneumonia (n = 66), representing 54% of all the neonatal deaths.…”
Section: Discussionmentioning
confidence: 64%
“…The most frequently reported causes of neonatal deaths are infections, perinatal asphyxia, metabolic diseases, and congenital malformations. [9–12]…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 12.2% of newborns die daily, and 37 neonates die per 1,000 live births [ 15 , 16 ]. High infant mortality occurred in the Afar and Oromia regional states of Ethiopia [ 17 ]. Studies done in Eastern Ethiopia show that 53.0% and 47.0% of infants’ deaths occur in the neonatal and post-neonatal periods respectively [ 17 ].…”
Section: Introductionmentioning
confidence: 99%